A critical assessment of ionic liquid-based aqueous biphasic systems for biomolecules extraction and CO2 absorption - Viggy Wee Gee Tan; Yazan Abuhasheesh; Doris Ying Ying Tang; Yongyu Zhang; Zengling Ma; Lin Chen; Rambabu Krishnamoorthy; Pau Loke Show (Chemical Engineering Journal Advances)
Ionic liquids (ILs) are green designer solvents that have gained research interest in industrial applications, including solvent chemistry, catalysis, and electrochemistry. Recent advances in ionic liquid-based aqueous biphasic systems (IL-ABSs) have broadened their biological applications. This review discusses the state-of-the-art of its biotechnological application in biomolecules recovery and phase separation mechanism. The prospects of ILs as green solvents and their toxicity and applicability in carbon dioxide (CO2) capture are discussed. The correlation between the structures and toxicity of ILs is also provided, with a special emphasis on the synthesis of safer ILs. This review examines the significance and techniques in recovering and reusing phase-forming agents such as ILs. The incorporation of machine learning (ML) algorithms to predict the toxicity and CO2 capture properties, as well as the scaling up of IL-ABSs, is also explored.